OPTIMALISASI LIMBAH TERNAK MENJADI PUPUK ORGANIK DI KELOMPOK TANI DAN TERNAK DESA MANGARAN KABUPATEN SITUBONDO - Kristian Kusumo Dirjo; M. Nur Rosyid Ridho; Diah Atika Sari; Fitri Nur Indah Fatika Sari; Aditya Pratama Mukti; Kharisma Wahyu Lestari; Ariska Sayyidaturrohmah; Dwiki Syahrul Ramadhan; Khofifah Tri Ambarwati; Ayu Asmita; Haryadi, Nanang Tri (PAPUMA: Journal of Community Services, 2026)
The development of the agricultural and livestock sectors in Mangaran Village has been relatively high, as indicated by livestock ownership involving 421 households with a total of 774 animals. While the livestock sector provides economic benefits, it also generates various problems arising from farming activities, particularly the accumulation of livestock manure. Based on field observations, it was found that most independent livestock farmers lack adequate knowledge regarding proper livestock waste management techniques. In response to these issues, one potential solution is the optimization of livestock waste as a raw material for producing bokashi organic fertilizer, which can be utilized as an agricultural input. This community service activity aimed to: (1) provide knowledge on the advantages and methods of producing bokashi from livestock manure, (2) increase public awareness of the importance of environmental cleanliness through proper livestock waste management, and (3) promote community self-reliance in fertilizer production. The target beneficiaries of this activity were farmers and livestock groups in Mangaran Village, Situbondo.The program was implemented through several stages, including field surveis, socialization and training, and mentoring activities. The results indicated that the community experienced an improvement in knowledge and skills related to livestock waste management, particularly in processing cattle manure into bokashi organic fertilizer.